Values of Life in Mitch Albomâ€™s â€œTuesday With Morrieâ€ - Gusti Ayu Made Rai Suarniti (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2019)
The title of this research is Values of Life in Mitch Albom’s Tuesday With Morrie. This research focuses on analyzing the types of values which are found in novel Tuesday With Morrie. This study aims to analyze the types of value of live on the novel Tuesday With Morrie and describe its implementation in human’s life. There are four methods of research used in this paper, they are: finding data resource, collecting and clasifying the data, analyzing the data, and the last is presenting the result of the analysis. All of the data used in the research are taken from Albom’s Tuesday With Morrie. The result of the analysis showed that in general there are two kinds of value found, they are entertainment value and educational value. Based on the educational value, there are three values found, such as society and civilizations value, moral – ethic – religion value, and practical value. The result of the study also showed that all of the all datacan be implemented in daily human’s life.